A Legal-Economic Analysis of Industrial Compliance in Waste Management Hazardous Chemicals and Estimating the Social Costs of Regulatory Non-Compliance - Angeli Dwi Agustin; Rhesas Shalatan; Abel Rayhan Merdeka Setiawan; Tengku Niesrina Syakira; Naufal Raki Pratama (Menulis: Jurnal Penelitian Nusantara, 2026)
This study aims to analyze industry compliance in the management of hazardous chemical waste from an economic law perspective and to examine estimates of the social costs resulting from regulatory noncompliance. This paper adopts a qualitative method using a literature review approach through the analysis of scientific literature and relevant regulations. The results of the study indicate that although Indonesia has fairly adequate regulations for the management of hazardous chemical waste, the level of industry compliance is still influenced by economic considerations, particularly the comparison between compliance costs and the risk of sanctions. Industrial non-compliance generates negative externalities in the form of environmental pollution and increased social costs borne by the public. Therefore, strengthened law enforcement, effective oversight, and the implementation of more transparent environmental accounting are necessary to reduce the social costs resulting from regulatory non-compliance.